The amyotrophic lateral sclerosis 8 protein, VAP, is required for ER protein quality control. - Moustaqim-Barrette, A.; Lin, Y.Q.; Pradhan, S.; Neely, G.G.; Bellen, H.J.; Tsuda, H. (Human Molecular Genetics, 2014)
A familial form of Amyotrophic lateral sclerosis (ALS8) is caused by a point mutation (P56S) in the vesicle-associated membrane protein associated protein B (VapB). Human VapB and Drosophila Vap-33-1 (Vap) are homologous type II transmembrane proteins that are localized to the ER. However, the precise consequences of the defects associated with the P56S mutation in the endoplasmic reticulum (ER) and its role in the pathology of ALS are not well understood. Here we show that Vap is required for ER protein quality control (ERQC). Loss of Vap in flies shows various ERQC associated defects, including protein accumulation, ER expansion, and ER stress. We also show that wild type Vap, but not the ALS8 mutant Vap, interacts with a lipid-binding protein, Oxysterol binding protein (Osbp), and that Vap is required for the proper localization of Osbp to the ER. Restoring the expression of Osbp in the ER suppresses the defects associated with loss of Vap and the ALS8 mutant Vap. Hence, we propose that the ALS8 mutation impairs the interaction of Vap with Osbp, resulting in hypomorphic defects that might contribute to the pathology of ALS8.